1) Cумма целых чисел с промежутка (-9; 4]: -8 + (-7) + (-6) + (-5) + (-4) + (-3) + (-2) + (-1) + 1 + 2 + 3 + 4 = = -26.
ответ: -26;
2) Сумма целых чисел с промежутка [-4 3/7; 3 1/9]: -4 + (-3) + (-2) + (-1) + 1 + 2 + 3 = -10 + 6 = -4.
ответ: -4;
3) Сумма целых чисел с промежутка [-6; 8] = (-6) + (-5) + (-4) + (-3) + (-2) + (-1) + 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 = 7 + 8 = 15;
ответ: 15;
4) Найдем сумму целых чисел с промежутка (-1,25;11,7]: -1 + 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 + 10 + 11 = 65;
ответ: 65
Пошаговое объяснение:
6х - 3х - 12 = 23 - 2х
3х + 2х = 23 + 12
5х = 35
х = 35 : 5
х = 7
4х + 3 * (х - 3) = 40
4х + 3х - 9 = 40
7х = 40 + 9
7х = 49
х = 49 : 7
х = 7